Debt Management Performance Assessment : Sierra Leone - World Bank (Washington, DC, 2013)
The results of this assessment show that seven (7) indicators warranted an overall score of C or better, demonstrating compliance with the minimum requirement; these referred to the debt management strategy; evaluation of debt management operation; coordination with fiscal policy; domestic borrowing; external borrowing; debt records and debt reporting, and debt administration and data security. A total of eight (8) indicators did not meet the minimum requirement at the time of the mission. These correspond to legal framework; managerial structure; audit, coordination with monetary policy; loan guarantees and on-lending; cash-flow forecasting and balance management; segregation of duties, staff capacity and business continuity and debt reporting. The mission notes that Ministry of Finance and Economic Development, or MOFED is currently implementing reforms in the areas of public debt management and domestic debt market development, including i) designing a new comprehensive public debt law; ii) implementing the reorganization of the debt management unit in MOFED; iii) formulating and implementing a procedures manual for debt management functions in MOFED; iv) implementing connectivity between two major data bases, namely CSDRMS and the integrated financial management system of the government. As a consequence, the mission expects several of these indicators to improve with reform implementation.